A Framework for Naming the Scope and Nature of Teacher Candidate Supervision in Clinically-Based Teacher Preparation: Tasks, High-Leverage Practices, and Pedagogical Routines of Practice. Issue 2 (2nd April 2020) - Burns, Rebecca West; Jacobs, Jennifer; Yendol-Hoppey, Diane
Abstract: This study introduces the scope and nature of teacher candidate (TC) supervision in an era of clinically-based teacher preparation. The findings emerged from a qualitative meta-analysis of 82 articles related to TC supervision published between 2001 and 2017. The study recognizes core supervision concepts drawn from decades of empirical literature yet moves the field substantially forward by identifying a framework that includes: (1) tasks, (2) high-leverage practices, and (3) pedagogical routines of supervisory practice. This framework defines a new understanding of how supervisors support TC learning throughout their clinical experiences. By naming the scope and nature of TC supervision, the framework of tasks, high-leverage practices, and pedagogical routines of supervisory practice can help supervisors become more conscious and more skilled about their practice to develop their professional vision of supervision. The framework can also guide the evaluation and re-design of TC supervision within clinically based teacher preparation.